2021
DOI: 10.5433/1679-0359.2021v42n3p1147
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization with estradiol benzoate in the presence of the corpus luteum in Wagyu cows increases the number of medium follicles but does not interfere with in vitro production of embryos

Abstract: Reproductive biotechnologies are emerging as an important element for livestock; however, some strategies must be modified to adapt to different breeding systems, such as the use of follicular synchronization protocols. This study aimed to evaluate follicular synchronization using estradiol benzoate (EB), in the presence of the corpus luteum (CL) from Wagyu oocyte donors in in vitro embryo production (IVEP). Rounds of IVEP were performed in heifers and cows (n=19) that were classified into three groups: G1/CL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…However, it is reported that despite the significant effects found, the values obtained in this study are similar to those reported in other studies carried out with Wagyu donor cows. In a study whose objective was to investigate the follicular synchronization using estradiol benzoate, with the presence of the corpus luteum, in bovine female donors of Wagyu oocytes, in in vitro embryo production, Zamai et al (2021) observed total oocyte values between 10.50 and 12.83, viability rate around 74%, total embryos produced between 2.40 to 2.85 and blastocyst rate between 19.16 to 26.44%. However, it is considered that the number of total and viable oocytes obtained in the studies Zamai et al (2021), regardless of treatment, was lower than those reported in the literature for other races (SARTORI et al, 2016), showing an inferiority in this aspect for Wagyu donors.…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is reported that despite the significant effects found, the values obtained in this study are similar to those reported in other studies carried out with Wagyu donor cows. In a study whose objective was to investigate the follicular synchronization using estradiol benzoate, with the presence of the corpus luteum, in bovine female donors of Wagyu oocytes, in in vitro embryo production, Zamai et al (2021) observed total oocyte values between 10.50 and 12.83, viability rate around 74%, total embryos produced between 2.40 to 2.85 and blastocyst rate between 19.16 to 26.44%. However, it is considered that the number of total and viable oocytes obtained in the studies Zamai et al (2021), regardless of treatment, was lower than those reported in the literature for other races (SARTORI et al, 2016), showing an inferiority in this aspect for Wagyu donors.…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 99%
“…In a study whose objective was to investigate the follicular synchronization using estradiol benzoate, with the presence of the corpus luteum, in bovine female donors of Wagyu oocytes, in in vitro embryo production, Zamai et al (2021) observed total oocyte values between 10.50 and 12.83, viability rate around 74%, total embryos produced between 2.40 to 2.85 and blastocyst rate between 19.16 to 26.44%. However, it is considered that the number of total and viable oocytes obtained in the studies Zamai et al (2021), regardless of treatment, was lower than those reported in the literature for other races (SARTORI et al, 2016), showing an inferiority in this aspect for Wagyu donors. However, despite this finding, the other reproductive advantages of Wagyu females stand out, such as sexual precocity, ease of delivery, maternal ability and longevity.…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 99%